Transaksi Nilai dalam Pendidikan Islam Pendekatan Ekonomi (Studi Pemikiran Muhammad Dawam Rahardjo) - Mukmin; Duraesa, M. Abzar; Zainuri, Habib (Universitas Majalengka, 2023)
This research aims to conduct an in-depth review of Dawam Rahardjo's thoughts, focusing on the concept of value transactions in Islamic education from an economic perspective, through critical analysis of his works. The research method used is a qualitative study that focuses on an in-depth analysis of Dawam Rahardjo's thoughts on value transactions in Islamic education, The qualitative approach allows a detailed and contextual investigation into the understanding of these values. The result of the study is to highlight the importance of practice in strengthening students' understanding of moral values. In the value transaction stage, Islamic economic values are not only useful in the economic context, but also become effective guidelines in shaping the moral character of individuals in accordance with Islamic principles. This research provides a more holistic view of how the value transaction process in education becomes an important foundation for the formation of moral, responsible and ethical individuals in everyday life.